2016
DOI: 10.1021/acs.joc.6b01997
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Homocitric Acid Lactone

Abstract: A short, diastereoselective synthesis of homocitric acid lactone is described. The key step is a bioinspired aldol addition to set the stereogenic center in an intermediate that requires only modest oxidation state manipulation to complete the synthesis. This approach enables rapid generation of isotopomers in which carbon and hydrogen can be replaced by heavier nuclei at nearly every position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…All reagents were purchased from commercial suppliers and used without further purification. (R)-3-Acetyl-4benzyl-2-oxazolidinone (S3) was synthesized according to Nickerson et al (Nickerson et al, 2016) and the spectra matched reported literature values (Ager et al, 1996). Reaction progress was monitored by thin-layer chromatography on silica gel 60 plates (aluminum back, EMD Millipore) and visualized by UV light or stained with KMnO4.…”
Section: General Synthetic Methodsmentioning
confidence: 93%
“…All reagents were purchased from commercial suppliers and used without further purification. (R)-3-Acetyl-4benzyl-2-oxazolidinone (S3) was synthesized according to Nickerson et al (Nickerson et al, 2016) and the spectra matched reported literature values (Ager et al, 1996). Reaction progress was monitored by thin-layer chromatography on silica gel 60 plates (aluminum back, EMD Millipore) and visualized by UV light or stained with KMnO4.…”
Section: General Synthetic Methodsmentioning
confidence: 93%
“…General synthetic methods: All reagents were purchased from commercial suppliers and used without further purification. (R)-3-Acetyl-4benzyl-2-oxazolidinone (S3) was synthesized according to Nickerson et al (Nickerson et al, 2016) and the spectra matched reported literature values (Ager et al, 1996). Reaction progress was monitored by thin-layer chromatography on silica gel 60 plates (aluminum back, EMD Millipore) and visualized by UV light or stained with KMnO4.…”
Section: Site Directed Mutagenesis Identificationmentioning
confidence: 93%
“…This compound 42.3 was converted to homocitric acid lactone 42.4 in 71% yield by hydrolysis of the aldol adduct to the methyl ester using sodium methoxide, followed by oxidative cleavage and hydrolysis with acid (Scheme 42). [52] …”
Section: Oxazolidinone Chiral Auxiliaries‐induced Asymmetric Synthesismentioning
confidence: 99%